2020
DOI: 10.1161/circgen.120.002969
|View full text |Cite
|
Sign up to set email alerts
|

Categorized Genetic Analysis in Childhood-Onset Cardiomyopathy

Abstract: Background - Childhood-onset cardiomyopathy (CMP) is a heterogenous group of conditions the etiology of which is largely unknown. The influence of consanguinity on the genetics of CMP has not been addressed at a large scale. Methods - To unravel the genetic etiology of childhood-onset CMP in a consanguineous population a categorized approach was adopted. Cases with childhood-onset CMP were consecutively recruited. Based on the likelihood of founder muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 27 publications
1
26
1
Order By: Relevance
“…WES in parent-offspring trios provides an efficient means to discover the genetic basis of DCM and ultimately enhances the yield of molecular diagnostics, as demonstrated in our case, which supports the previous findings reported by prior studies [ 9 , 10 , 11 ]. Pathogenic variants of the RPL3L sequence associated with neonatal DCM in both siblings in our report were determined by the criteria laid out by the American College of Medical Genetics and Genomics and the Association for Molecular Pathology [ 12 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…WES in parent-offspring trios provides an efficient means to discover the genetic basis of DCM and ultimately enhances the yield of molecular diagnostics, as demonstrated in our case, which supports the previous findings reported by prior studies [ 9 , 10 , 11 ]. Pathogenic variants of the RPL3L sequence associated with neonatal DCM in both siblings in our report were determined by the criteria laid out by the American College of Medical Genetics and Genomics and the Association for Molecular Pathology [ 12 ].…”
Section: Discussionsupporting
confidence: 90%
“…The reason for the high diagnostic product by NGS is that commercially available genetic panel tests would not test some of the newly reported gene variants. Al-Hassnan et al have indicated that when there is a strong suspicion of a genetic etiology in a family with cardiac disease, NGS such as WES/WGS should be considered a first-line test [ 10 ]. We report autosomal recessively inherited compound heterozygous variants of RPL3L (ribosomal protein L3-like) in two affected siblings using WES.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic testing in individuals with DCM with a positive family history of cardiomyopathy identifies causative mutations in only approximately 25% [ 7 ]. Currently, if there is no family history and no known genetic mutation is suspected, using WES as a first-line genetic test to identify the underlying etiology for DCM is recommended [ 8 ]. In contrast to other types of genetic testing, WES sequences thousands of genes simultaneously rather than analyzing one or a few genes.…”
Section: Discussionmentioning
confidence: 99%
“…The second describes p.Ala1152Thr and p.Thr618Ile variants in a patient with multiple congenital anomalies without intellectual disability, including hyperextensible skin, thoracolumbar scoliosis, and myopathy. Both studies did not prove the causality and pathogenicity of the identified variants; the mutations and the gene were classified as candidates [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%